Personality traits, knowledge, practice and logistic with work performances as indicator of Youth Productive Malaysian Cocoa Farmers (YPMCF) well being - Sulaiman, Winoryantie; Ariff Shah, Jasmin; Muhamed Haris, Nurbahiah (Human Resources Management Academic Research Society (HRMARS), 2022)
Community wellbeing is depends on individual levels of people who belong to the community and also on research purpose and interest. Work performance of cocoa farmers has played a significant role in contributing cocoa production in Malaysia since 2006. The low production was reported due to the low productivity of cocoa beans produced by the farmers. Productivity in 2020 was 0.19 tonne, which means 38% achieved from the expected outcome. Cocoa farmers play significant roles in determining the high yield of their cocoa farm. Youth involvement in agriculture sector especially cocoa plantation is a crucial challenge not only in Malaysia but also worldwide. To achieve the sustainable improvement on cocoa production, there is a need to find the factors that influence the existing Youth Productive Malaysian Cocoa Farmers (YPMCF) performances. Therefore, the objectives of this article are i) To determine the level of Personality Traits, Knowledge, Practice and Logistic and work performances ii) To determine the relationship between Personality Traits, Knowledge, Practice and Logistic with work performances of YPMCF iii) To determine the most influential factors (IVs) toward work performances of YPMCF. This study driven from Iceberg Model. A total number of 40 YPMCF were involved in this purposive data collection which are only 11.46% from the samples population. Data analyses have been conducted using IBM SPSS Software. Results found that only decision and discipline produce high level indicator, and all the variables showed the positive and strong correlation. Factors that contribute to YPMCF work performances are Practice and Logistic.